2009
DOI: 10.1007/s10517-010-0819-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liposomes of Different Lipid Composition on In Vitro Growth of Mycobacterium Tuberculosis H37Rv

Abstract: The growth of M. tuberculosis H37RV in culture medium was studied after addition of liposomes from different lipids (phosphatidylcholine, cardiolipin, and glycosphyngolipids). Addition of phosphatidylcholine into culture medium did not modify the growth and multiplication of mycobacteria. Addition of glycosphyngolipids and their mixture with phosphatidylcholine partially inhibited the growth. Addition of cardiolipin inhibited the growth of mycobacteria and even suppressed it, depending on the dose. Presumably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Applying Murohashi staining method we demonstrated that such concentration of CL cause lysis of M. tuberculosis H37Rv cells (fig. 5) [Sorokoumova, 2009]. Fig.…”
Section: An Effect Of Lipids On Growth and Viability Of Mycobacterium Tuberculosis H37rvmentioning
confidence: 97%
See 1 more Smart Citation
“…Applying Murohashi staining method we demonstrated that such concentration of CL cause lysis of M. tuberculosis H37Rv cells (fig. 5) [Sorokoumova, 2009]. Fig.…”
Section: An Effect Of Lipids On Growth and Viability Of Mycobacterium Tuberculosis H37rvmentioning
confidence: 97%
“…Reproduced from [Sorokoumova, 2009] # Lipid 2-H37Rv+CL (50 µg/ml); 3-H37Rv+CL (750 µg/ml). Reproduced from [Mikulovish, 2010] These data correlate well with the results of mycobacterial DNA detection by real time PCR, according to which appearance CL in culture medium didn't lead to increase of DNA number [Sorokoumova, 2009] (fig. 6).…”
Section: An Effect Of Lipids On Growth and Viability Of Mycobacterium Tuberculosis H37rvmentioning
confidence: 99%
“…Applying Murohashi staining method we demonstrated that such concentration of CL cause lysis of M. tuberculosis H37Rv cells ( fig. 5) [Sorokoumova, 2009]. Reproduced from [Sorokoumova, 2009] 2-H37Rv+CL (50 µg/ml); 3-H37Rv+CL (750 µg/ml).…”
Section: An Effect Of Lipids On Growth and Viability Of Mycobacteriummentioning
confidence: 99%
“…Reproduced from [Sorokoumova, 2009] 2-H37Rv+CL (50 µg/ml); 3-H37Rv+CL (750 µg/ml). Reproduced from [Mikulovish, 2010] These data correlate well with the results of mycobacterial DNA detection by real time PCR, according to which appearance CL in culture medium didn't lead to increase of DNA number [Sorokoumova, 2009] (fig. 6).…”
Section: An Effect Of Lipids On Growth and Viability Of Mycobacteriummentioning
confidence: 99%
See 1 more Smart Citation